Evolutionary Stages of Feminine Consciousness in "Makhota" - Shahzad, Muhammad Kamran; Riaz, Farzana; Saddiq, (Makhz (Research Journal), 2024)
A woman is a precious gift of nature in the form of a mother, sister, wife and daughter, without which the beauty of the universe would fade away, but even in the civilized societies of the world, instead of fulfilling the rights of women, they are oppressed. Due to this, women feel insecure in the society.Due to this insecurity, the female fiction writers of Urdu literature have criticized women's rights in their stories.Among these female fiction writers, Dr. Najiba Arif's name needs no introduction.You have a strong identity as a teacher, linguist, poet and novelist. His first novel "Makhota" was published in 2023 by Aks Publishers Lahore. In the novel, the author has addressed the deprivation of the poor women and their active role in the society. In this paper, the female consciousness of the author has been analyzed in the novel.